2020
DOI: 10.1007/s40200-020-00494-4
|View full text |Cite|
|
Sign up to set email alerts
|

Adjusted tight control blood glucose management in diabetic patients undergoing on pump coronary artery bypass graft. A randomized clinical trial

Abstract: Background Many of the patients who are undergoing Coronary Artery Bypass Graft have diabetes mellitus or metabolic syndrome and are at risk for hyperglycemia events.Objective The present study aimed to compare conventional glucose control with adjusted tight control in patients undergoing on-pump CABG. Methods This double -blind randomized clinical trial study was conducted in Shiraz, Iran, from September 2017-March 2018. Two consecutive groups of 75 patients undergoing elective on-pump coronary artery bypass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The GLUCO-CABG trial compared intensive sugar control (100–140 mg/dL) with regular sugar control (141–180 mg/dL) and revealed no significant difference in perioperative complications between the two strategies ( 212 ). Two of the studies included in our analysis defined the intensive sugar control level as 80–110 and 100–120 mg/dL, respectively ( 121 , 178 ). Because the results of our NMA revealed that intensive sugar control is ineffective in preventing post–cardiac surgery AKI and is potentially associated with a higher risk of hypoglycemia and mortality, we argue that intensive sugar control should be applied with caution.…”
Section: Discussionmentioning
confidence: 99%
“…The GLUCO-CABG trial compared intensive sugar control (100–140 mg/dL) with regular sugar control (141–180 mg/dL) and revealed no significant difference in perioperative complications between the two strategies ( 212 ). Two of the studies included in our analysis defined the intensive sugar control level as 80–110 and 100–120 mg/dL, respectively ( 121 , 178 ). Because the results of our NMA revealed that intensive sugar control is ineffective in preventing post–cardiac surgery AKI and is potentially associated with a higher risk of hypoglycemia and mortality, we argue that intensive sugar control should be applied with caution.…”
Section: Discussionmentioning
confidence: 99%
“…These may limit the use of intralipid on-pump CABG. However, Javaherforoosh Zadeh et al [ 66 ] showed that using adjusted tight glycemic control to a level that is near to normal during cardiac surgery may reduce hyperglycemic complications. Due to the lack of research on proper intravenous dosage of intralipid in lung injury after CPB, more data are needed to confirm the specific dose to be used.…”
Section: Discussionmentioning
confidence: 99%
“…Studies estimated a prevalence of 30-40% for diabetes mellitus in patients undergoing coronary artery bypass grafting (CABG). 2 , 3 Diabetic patients undergoing CABG have a higher risk of postoperative morbidity and mortality, stroke, renal failure, infections, recurrent episodes of angina and readmission for cardiac-related issues or other causes. So that, increases in blood glucose levels before, during and immediately after surgery predict elevated perioperative complications in patients undergoing cardiovascular surgery; therefore, hyperglycemia is regarded as an indicator of poor outcomes among these patients.…”
Section: Introductionmentioning
confidence: 99%